APPLYING ELECTRICAL RESISTIVITY TOMOGRAPHY FOR AGRICULTURAL LAND ASSESSMENT TO SUPPORT CROP SELECTION: A CASE STUDY IN RUMAH TIGA VILLAGE, MALUKU - Parnadi, Wahyudi Widyatmoko; Tuhumury, Grace; Bahri, Samsul (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The declining productivity of the agricultural sector in Maluku Province poses a serious challenge, partly due to the limited availability of scientific data on agricultural land characteristics to support precision agriculture. This study aimed to develop a subsurface resistivity model and evaluate farmland suitability in Rumah Tiga Village, Ambon Island, Maluku. Electrical Resistivity Tomography (ERT) with the Wenner configuration was applied along eight survey lines, supported by laboratory analyses of porosity, water content, specific gravity, soil texture, and pH. The modelling results revealed three major resistivity zones: water-saturated clay (<20 Ωm), sandy gravel (20–33.8 Ωm), and boulders (>70 Ωm). The distribution map of soil parameters showed significant spatial variability, and further analysis demonstrated clear relationships between resistivity data and soil physical properties. Land suitability evaluation identified three classifications based on crop water requirements, covering a total area of 6,684 m²: Area I (46.72%, 3,123 m²), suitable for crops with high water demand such as rice and leafy vegetables; Area II (23.78%, 1,971 m²), suitable for crops with medium water demand such as tomatoes, chillies, and corn; and Area III (29.50%, 1,590 m²), suitable for crops with low water demand such as tubers and legumes. This research provides a scientific basis for sustainable agricultural planning and the implementation of precision agriculture in Ambon and its surrounding areas.